[PP.05.26] A SYSTEMATIC REVIEW OF TELEMONITORING ASSESSMENT FOR PATIENTS WITH HEART FAILURE. (September 2017) - Farnia, T.; Jaulent, M.-C.; Steichen, O.
Abstract : Objective: Telemonitoring (TLM) can improve heart failure (HF) management but there is no standardized evaluation framework to comprehensively evaluate the various impacts of TLM. Our objectives were to list the criteria used in published evaluations of HF TLM projects, to describe how these criteria are used in the evaluation studies, and to organize these criteria into a comprehensive evaluation framework. Design and method: Articles were obtained through the Medline, Web of Science and Embase from 1990 to August 2015. Articles were eligible if they were original reports of a HF TLM evaluation study in English language. Studies of implantable TLM devices were excluded. Each selected article was screened to extract the description of the TLM project, and of the evaluation process and criteria. A qualitative synthesis was performed. Results: Overall, 121 articles were selected and reviewed, leading to 52 evaluation criteria classified along six dimensions: technical, economic, educational, clinical, organizational and users' perspectives. The clinical and economic impacts were evaluated in over 65% of studies whereas the educational, organizational and technical impacts were studied in less than 15%. The clinical and economic impacts were studied in over 65% of studies whereas the educational, organizational and technical impacts were studied in less than 15%. Users' perspective was the most frequently covered dimension in the development phase of TLM projects, whereas study of the clinical and economic impacts were dominating in later phases. Conclusions: TLM evaluation frameworks should cover all of the six dimensions, appropriately distributed along the TLM project life cycle. Our next goal is to build such a comprehensive evaluation framework for TLM and to test it on an ongoing TLM project.